Fibromyalgia and Headaches - Rocha-Filho, Pedro Augusto Sampaio (Headache Medicine, 2013)
Fibromyalgia is characterized for chronic widespread musculoskeletal pain for which no tissue inflammation or damage can be identified. This review aims to examine the studies on fibromyalgia and headache focusing on prevalence, pathophysiology and clinical features. Population studies show that fibromyalgia is a comorbidity of migraine and tension-type headache. Fibromyalgia prevalence in migraine and tension-type headache patients from headache and pain clinics varies from 9.8% to 35.6% and from 35% to 59%, respectively. Chronic forms of migraine and tensiontype headache show a high frequency of fibromyalgia comorbidity and central sensitization could be the link among these conditions. Patients with primary headaches and fibromyalgia have a higher impact of both conditions.